(untitled) (GnosisWisdom, 2025)
The cultivation of tara (Caesalpinia spinosa), a leguminous species of high ecological and commercial value in the Peruvian Andes, faces increasing phytosanitary pressure from pests such as Aethalion reticulatum, Freysuila caesalpiniae, Aphis craccivora, and ants of the genus Acromyrmex. These pests cause various types of damage, such as sap sucking, virus transmission, leaf deformation, defoliation, and sooty mold proliferation, affecting the physiology and quality of the products (tannins, gum, seeds) and the profitability of the crop. The state of the art was reviewed in its heuristic and hermeneutic phases, using databases such as Scopus, SciELO, Google Scholar, and university repositories, from which references from the last five years were extracted. The contents of these references recorded research aimed at identifying the agronomic and economic impacts of these pests, as well as their respective control through chemical, biological, cultural, and genetic strategies. The evidence highlights the urgent need to implement Integrated Pest Management strategies adapted to Andean agroecological conditions, prioritizing monitoring, biological control, and sustainable practices. Among the conclusions, it is highlighted that pests reduce physiological vigor, decrease fruit, tannin, and tara gum yields, compromising the profitability of producers, especially in Andean regions.